2016
DOI: 10.1038/srep38083
|View full text |Cite
|
Sign up to set email alerts
|

Targeting intracellular p-aminobenzoic acid production potentiates the anti-tubercular action of antifolates

Abstract: The ability to revitalize and re-purpose existing drugs offers a powerful approach for novel treatment options against Mycobacterium tuberculosis and other infectious agents. Antifolates are an underutilized drug class in tuberculosis (TB) therapy, capable of disrupting the biosynthesis of tetrahydrofolate, an essential cellular cofactor. Based on the observation that exogenously supplied p-aminobenzoic acid (PABA) can antagonize the action of antifolates that interact with dihydropteroate synthase (DHPS), suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
(39 reference statements)
2
25
0
1
Order By: Relevance
“…Previously, Thiede et al reported that disruption of pABA biosynthesis potentiates the antitubercular effect of anti-folates by up to 1,000-fold (33). Here, we showed that SigB regulates the expression of pabB gene in M. tuberculosis and, as a result, deletion of sigB results in decreased expression of pabB, impaired pABA production, and increase susceptibility to antifolates.…”
Section: Discussionsupporting
confidence: 58%
“…Previously, Thiede et al reported that disruption of pABA biosynthesis potentiates the antitubercular effect of anti-folates by up to 1,000-fold (33). Here, we showed that SigB regulates the expression of pabB gene in M. tuberculosis and, as a result, deletion of sigB results in decreased expression of pabB, impaired pABA production, and increase susceptibility to antifolates.…”
Section: Discussionsupporting
confidence: 58%
“…Since the non-pathogenic mycobacterium, Mycobacterium smegmatis (Ms), is resistant to PAS, we determined if PAS could be utilized in a M. tuberculosis Δ pabB strain expressing in trans folAMtb or folA from M. smegmatis (folAMs). M. tuberculosis Δ pabB strain expressing folAMtb grew only in the presence of PABA, not PAS (Extended Data Figure 2a) 15 . Interestingly, M. tuberculosis Δ pabB expressing folAMs grew in the presence of both PAS and PABA (Extended Data Figure 2).…”
mentioning
confidence: 99%
“…Since SMX treatment has previously been shown to increase PABA production in bacteria, we reasoned that SMX is causing an increase in PABA biosynthesis and, thereby, antagonism of PAS 17 . Previous work has shown that strains lacking pabB in M. tuberculosis are PABA auxotrophs and can only grow with exogenously added PABA 15 .…”
mentioning
confidence: 99%
“…Algunos antibacterianos como las sulfonamidas compiten con el PABA por medio de la inhibición de la enzima dihidrofolato reductasa necesaria para el paso de dihidrofolato a tetrahidrofolato, cofactor necesario en la síntesis de DNA y proteínas. La resistencia bacteriana se presenta por mutación espontánea o transferencia de la misma a través de plásmidos, generando mutación de la dihidroteroato sintetasa, creando una vía metabólica alterna para la sínte-sis del ácido fólico y generando aumento en la capacidad de inactivar o destruir la droga y producción de un antagonista de la droga (Thiede et al, 2016;Gardeweg, 2012). Se destaca, igualmente, la alteración enzimática del sitio objetivo del fármaco, reduciendo la afinidad del antibiótico al sitio blanco; estos mecanismos también son regulados por enzimas eritromicina metilasas ribosomales que otorgan resistencia a macrólidos (Sheldon).…”
Section: Mecanismos De Resistencia a Nivel Intracelularunclassified